Caries in Portuguese children with Down syndrome (Clinics, 2011)
OBJECTIVES: Oral health in Down syndrome children has some peculiar aspects that must be considered in the follow-up of these patients. This study focuses on characterizing the environmental and host factors associated with dental caries in Portuguese children with and without Down syndrome. METHODS: A sibling-matched, population-based, cross-sectional survey was performed. RESULTS: Down syndrome children presented a significantly greater percentage of children without caries, 78% vs. 58% of non-Down syndrome siblings. This difference in the DMFT index (number of decayed, missing and filled teeth) essentially reflects data obtained from treated teeth, for which 91% of children with Down syndrome had never had a tooth treated vs. 67% of siblings. This result was statistically significant, whereas results for decayed and lost teeth did not differ between Down syndrome children and their unaffected siblings. Additionally, in Down syndrome children, a delayed eruption of the second molar occurs. Down syndrome children and their siblings have similar oral hygiene habits, but a higher percentage of Down syndrome children visit a dentist before the age of three years, in comparison to their siblings. Bruxism was also more common in Down syndrome children compared to their siblings. CONCLUSIONS: Our results show that Portuguese children with Down syndrome have lower caries rates than children without Down syndrome. This reduced prevalence may be associated with the parents' greater concern about oral health care in Down syndrome children, resulting in their taking them sooner to visit a dentist, as well as to a higher bruxism prevalence and delayed tooth eruption.